Mygalomorph spider community of a natural reserve in a hilly system in central Argentina - Ferretti, Nelson Edgardo (2012)
The diversity, abundance, spatial distribution, and phenology of the mygalomorph spider community in the "Ernesto Tornquist" Strict Nature Reserve were analyzed in this study. Located in southwestern Buenos Aires, Argentina, the Reserve is representative of the Ventania system, which is a sigmoidal mountain belt 180 km in length. This exceptional hilly ecosystem is home for many endemic species and rich native fauna and flora. Spider abundance was sampled monthly from October 2009 to October 2010 by hand capture and pitfall traps on grassland slopes. The species recorded in the study area were: Actinopus sp.1 (Actinopodidae); Grammostola vachoni and Plesiopelma longisternale (Theraphosidae); Acanthogonatus centralis (Nemesiidae); and Mecicobothrium thorelli (Mecicobothriidae). Grammostola vachoni and Acanthogonatus centralis were the dominant species in hand capture and pitfall traps, respectively. The seasonal variation, diversity, and abundance of the mygalomorph community are analyzed and discussed here. The Mygalomorphae of the Ventania system comprises an important group of sedentary and cryptozoic spiders that seem to be highly dependent on habitat type and environmental factors.